EFL TEACHER’S PRACTICES IN UTILIZING ONLINE TEACHING RESOURCES FOR READY-MADE CLASSROOM TASKS - Wibowo, Enggar Pangesti (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2026)
Teachers in Indonesia often face a high administrative burden, leaving them with lack time and energy to prepare classroom tasks. Although technology comes as a solution to ease teachers’ workload, its utilisation is still not optimal. This study aims to explore what online teaching resources that EFL teacher uses to provide ready-made worksheets, how the teacher utilises the resources, and her perceptions and experiences of the advantages and disadvantages of each platform. This study used a qualitative case study design involving one English teacher in one public junior high school in Semarang, Central Java. Data were collected through interviews and documentation. The results show that the teacher employed Twinkl, ISLCollective, Liveworksheets, and Canva-with Twinkl being the most frequently used platform-to download worksheets which are sometimes modified before being given to students. The teacher found them helpful although each has its own advantages and disadvantages in terms of visual appearance and accessibility. Unfortunately, support from school for covering the premium subscription costs remains limited due to constrained operational budgets. Therefore, more adequate support is needed so that the use of technology can be optimised to support teachers' tasks on an ongoing basis.